PODEMOS PHENOMENON - S. . Khenkin (Ибероамериканские тетради)
The article studies political ideological orientations and practical steps taken by Podemos party, which was founded in January 2014 and for a short time turned into an influential actor in Spanish politics. Special attention is given to the Podemos image metamorphoses, designed to satisfy the interests of various groups of population with different political orientations.